Performance Evaluation of Dimoro Irrigation Area Based on Rating Scale Methods - Dian Retno Anugrah; Sobriyah Sobriyah; Dewi Handayani (International Journal of Science and Applied Science: Conference Series, 2017)
Sustainable operation and maintenance activities determine durability and success level of irrigation infrastructure. Success indicator of irrigation such as increasing of water usage efficiency, increasing of plant intensity, decreasing of water distribution conflict, increasing of agricultural production result and decreasing of dryness of plant. Therefore, it is necessary to have research to determine the performance of irrigation operation that had been carried out from 2013 – 2106 at Dimoro Irrigation Area. The Dimoro operational data records 2013 - 2016 were analyzed by simple weighting for each indicator, then analyzed to obtain performance for each year. The results showed that the operation irrigation at Dimoro Irrigation Area tend to succeed if seen from its performance that rises.